Temperature‐dependent thermal conductivity of flexible yttria‐stabilized zirconia substrate via 3ω technique (Phys. Status Solidi A 10∕2017). Issue 10 (12th October 2017) - Singh, Shivkant; Yarali, Milad; Shervin, Shahab; Venkateswaran, Venkat; Olenick, Kathy; Olenick, John A.; Ryou, Jae‐Hyun; Mavrokefalos, Anastassios
Abstract : With the advancement in Nano‐technology and the need for flexible electronics with high power densities, thermal management of such devices has become an important factor to ascertain their efficiency, safety and longevity. The hunt for flexible substrate materials with multi‐functional properties including flexibility, good optical properties and high heat dissipating capability is not a trivial task. Often, one functionality outweighs the other and hence, makes it difficult to find a material with optimal thermo‐opto‐electronic properties. Here, Shivkant et al. (article No. 201700069 ) present a novel state‐of‐the‐art flexible yttria‐stabilized zirconia based ceramic to address this issue. By manipulating the grain size, a thermal conductivity values exceeding 4 W m −1 K −1 could be obtained in this optically transparent, thin (only 40μm thick) yet roll‐to‐roll compatible flexible ceramic material. This allows these flexible substrates to have orders of magnitude higher thermal dissipation rates compared to polymer flexible substrates, which minimizes the degradation of high power optoelectronic devices due to thermal parasitic effects.